Entrepreneurship education, gender and family background as antecedents on the entrepreneurial orientation of university students - Marques, C. S. E.; Santos, G.; Galvão, A.; Mascarenhas, C.; Justino, E. (International Journal of Innovation Science, 2018)
Purpose - This study aims to evaluate the impact of entrepreneurship education (EE) on the entrepreneurial orientation (EO) of higher education students, as mediated by gender and family history. A survey tool for measuring EO was developed and used in one university. The responses were processed using statistical methods. Design/methodology/approach - The data were collected with an online questionnaire distributed to students of engineering and business and social sciences in the past year of their degree program at the undergraduate and graduate levels. Some respondents had a class in entrepreneurship, while others did not have it. Findings - The results highlight that EE generally has a greater impact on business and social sciences students. Family background and gender are moderating variables with a positive influence on individual entrepreneurial orientation (IEO). Practical implications - This study's main practical implication is that evidence was found that universities need to develop more effective didactic approaches to EE. These must take into account new market demands and students' profile and always taking into account their different academic areas and levels of previous EE. Originality/value - This paper contributes to filling a gap in the literature by identifying the importance of EE, gender and family background to the development of IEO in students of different academic programs (i.e. engineering, business and social sciences).